G135(P) Changing local policy on intravenous fluid choice; improving safety, cost-effectiveness and compliance with best practice. (12th March 2018) - MacCarrick, T; Ellis, R; Nelhans, N
Abstract : Aim: Using isotonic solution is considered best practice in the treatment of most children requiring intravenous fluids, in accordance with NICE guideline NG29. We observed that paediatric patients in this hospital frequently received 0.45% saline with additional glucose ±potassium for maintenance. Other fluid preparations frequently prescribed for children included 0.9% saline and Hartmanns Solution. Our aim was to develop a new guideline for intravenous fluid prescription which conformed to best practice and streamlined choice of solution. Methods: A review of evidence regarding use of isotonic fluids in paediatrics was undertaken. Based on this, the feasibility of introducing PlasmaLyte (with and without 5% glucose) was explored. Information concerning licensing, safety and cost-comparison with intravenous solutions currently used in the trust was reviewed. The acceptability of PlasmaLyte within the regional paediatric network was established. This information was presented to key stakeholders, followed by a proposal to introduce PlasmaLyte as the fluid of choice in all paediatric patients in the trust, unless specifically contraindicated. Results: PlasmaLyte is a balanced crystalloid licensed for intravenous use (with and without 5% glucose) in paediatrics, for bolus and maintenance infusion. An emerging body of evidence supports its clinical superiority when compared to other fluid preparations. There are, however, certain conditions, for example pyloric stenosis, in which PlasmaLyte is contraindicated. Although more expensive than saline solutions, taking into account the frequency of use of saline with additives, which is considerably more expensive, overall cost-comparison between PlasmaLyte and the fluid preparations currently used in this trust indicated that PlasmaLyte and PlasmaLyte with 5% glucose is more cost-effective. PlasmaLyte is already used by the regional paediatric transport service. Conclusion: PlasmaLyte (and PlasmaLyte with 5% glucose) constitutes a safe, cost-effective intravenous fluid for most paediatric patients, which conforms to best practice. Furthermore, streamlining of intravenous fluid choice both within the trust and the wider paediatric network reduces confusion, promoting safety and continuity of care. Overall, PlasmaLyte (and PlasmaLyte with 5% glucose) constitutes a suitable fluid of choice for use in all paediatric patients in the trust, unless specifically contraindicated.